The Chinese government's response to drug use and HIV/AIDS: A review of policies and programs - Zhang Cunmin; Ha Toan H; Li Jianhua; Liu Hongjie (BMC, 2010)
Abstract Illicit drug use has become popular in China. Acknowledging the challenge of illicit drug use, China has adopted several new policies on the management of illicit drug use in recent years. This study reviews the current policies on drug use and assesses the harm reduction interventions among drug users in China. The review documents that the new policies on drug use provide a variety of choices of detoxification treatment for drug users. The methadone maintenance treatment and needle exchange programs have been adopted as harm reduction models in China. Most of the reviewed harm reduction programs have been successfully implemented and yielded positive effects in reducing drug related risk behaviors among drug users. Although there remain barriers to the effective implementation of policies on drug use and harm reduction programs, Chinese government has shown their commitment to support the expansion of harm reduction interventions for drug users throughout the country.